Philosophical Foundations of Collective Responsibility on the Example of the Activities of the European Court of Human Rights - Zayets, Serghiy (Filosofiya osvity. Philosophy of Education, 2023)
The scale of the consequences caused by Russia’s aggression against Ukraine inevitably leads to reflections on the collective responsibility of Russian citizens. The philosophical justification of collective responsibility is still problematic. The main issues under debate are the possibility of the existence of collective social agents and collective guilt as a basis for imposing responsibility. This article proposes to look at the activities of the European Court of Human Rights as a practice of collective responsibility in international law. The activities of the European Court of Human Rights can serve as a practical benchmark for assessing certain theoretical positions. Important historical experience is provided by the practice of holding the international military tribunal in Nuremberg (Germany, November 20, 1945 – October 1, 1946), which had the status of an international court over the military and political leadership of Nazi Germany – known as the Nuremberg Trials. With this practical example of collective responsibility in mind, the study proposes to conduct a selective reverse review of the philosophical views of Hannah Arendt and Karl Jaspers. The study demonstrates that although the reflections of these philosophers were not without certain flaws, Arendt and Jaspers, focusing mainly on different aspects, were able to offer a generally sound justification for collective responsibility. Their proposed justification can serve as a foundation for further developments in this area. The practical significance of this conclusion is that it may give impetus to the development of new legal mechanisms of collective responsibility of the Russians for the consequences of their unjustified aggression against Ukraine. Such collective responsibility has not only legal, but also moral and political dimensions, and is also a component of the so-called social «educational process» (Lernprozess).